Autosomal genetic variation is associated with DNA methylation in regions variably escaping X-chromosome inactivation - René Luijk (Nature Portfolio, 2018)
DNA methylation is critically involved in X chromosome inactivation (XCI) and dosage compensation, yet some X-chromosomal genes escape XCI. Here, Lujik et al. identify three autosomal genetic loci that associate with differential DNA methylation near genes that variably escape XCI in females.